1998
DOI: 10.1128/aem.64.8.2899-2905.1998
|View full text |Cite
|
Sign up to set email alerts
|

Strain IMB-1, a Novel Bacterium for the Removal of Methyl Bromide in Fumigated Agricultural Soils

Abstract: A facultatively methylotrophic bacterium, strain IMB-1, that has been isolated from agricultural soil grows on methyl bromide (MeBr), methyl iodide, methyl chloride, and methylated amines, as well as on glucose, pyruvate, or acetate. Phylogenetic analysis of its 16S rRNA gene sequence indicates that strain IMB-1 classes in the alpha subgroup of the class Proteobacteria and is closely related to members of the genus Rhizobium. The ability of strain IMB-1 to oxidize MeBr to CO2 is constitutive in cells regardles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…Two more facultative methylotrophs capable of aerobic growth on both methyl chloride and methyl bromide as sole carbon and energy sources have been isolated recently. Strain IMB1 was isolated from soil that had been fumigated with methyl bromide (Miller et al , 1997; Connell Hancock et al , 1998), whereas strain CC495 was isolated from topsoil in a pristine woodland site (Coulter et al , 1999). These two strains were shown by 16S rRNA sequence analysis to be closely related to each other (Coulter et al , 1999) and to the Aminobacter genus (Kämpfer et al , 1999) (see Fig.…”
Section: Phylogenetic Diversity Of Methyl Halide‐degrading Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Two more facultative methylotrophs capable of aerobic growth on both methyl chloride and methyl bromide as sole carbon and energy sources have been isolated recently. Strain IMB1 was isolated from soil that had been fumigated with methyl bromide (Miller et al , 1997; Connell Hancock et al , 1998), whereas strain CC495 was isolated from topsoil in a pristine woodland site (Coulter et al , 1999). These two strains were shown by 16S rRNA sequence analysis to be closely related to each other (Coulter et al , 1999) and to the Aminobacter genus (Kämpfer et al , 1999) (see Fig.…”
Section: Phylogenetic Diversity Of Methyl Halide‐degrading Bacteriamentioning
confidence: 99%
“…Studies have shown that IMB‐1 is able to grow on methyl halides, methylated amines and non‐C1 compounds such as glucose, acetate and pyruvate (Connell Hancock et al , 1998), but no growth or oxidation was observed with methyl fluoride (MeF), methane, propyl iodide, dibromomethane, dichloromethane or difluoromethane (Miller et al , 1997; Connell Hancock et al , 1998; Schaefer and Oremland, 1999). Growth was observed with methyl bromide, methyl chloride and methyl iodide as sole carbon and energy sources.…”
Section: Biochemistry and Genetics Of Methyl Halide‐degrading Bacteriamentioning
confidence: 99%
“…An important sink in the environment for methyl halides is biological degradation, and bacteria have been isolated that use methyl halides as a sole source of carbon and energy. These include the terrestrial strains Methylobacterium chloromethanicum CM4 and Hyphomicrobium chloromethanicum CM2 [2,3], Aminobacter ciceronei IMB‐1 [4–6], Aminobacter lissarensis CC495 [6–8] and the marine strain Leisingera methylohalidivorans [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…A. lissarensis CC495 was isolated from the upper 5 cm of the soil horizon in a wood in County Down, Northern Ireland[7] and is closely related to A. ciceronei IMB‐1, a methyl halide degrader isolated from MeBr fumigated agricultural soil[5]. The physiology and biochemistry of methyl halide degradation in A. lissarensis CC495 has been studied [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The methyl group is next transferred to tetrahydrofolate by another methyltransferase (CmuB), and the methyl tetrahydrofolate is progressively oxidised to formate and CO 2 , with carbon assimilation at the level of methylene tetrahydrofolate (Vannelli et al ., ). Several species of bacteria that use this methyltransferase‐based pathway have been isolated from a range of environments, including soils, plant phyllosphere and the marine environment (Doronina et al ., ; Connell‐Hancock et al ., ; Goodwin et al ., ; Coulter et al ., ; Hoeft et al ., ; McAnulla et al ., ; Schaefer et al ., ; Borodina et al ., ; Schäfer et al ., ; Nadalig et al ., ). The unique structure of CmuA has been exploited to design primers for studying the diversity of methyl halide‐degrading bacteria in the environment (McDonald et al ., ; Miller et al ., ; Borodina et al ., ; Schäfer et al ., ; Nadalig et al ., ).…”
Section: Introductionmentioning
confidence: 99%